THE URGENCY OF ESTABLISHING REGIONAL REGULATIONS ON THEMATIC TOURISM IN SUMENEP REGENCY - Syarif, Yusmita; Ansori, Ansori (Faculty of Law Universitas Trunojoyo Madura, 2022)
Thematic tourism is a new term in the world of tourism that needs to be applied in today's life. Thematic tourism is a solution to current needs and also a development of the pre-existing tourism concept. Regulations both laws and local regulations on tourism already exist and are good. Meanwhile, the Sumenep Regency is an area that geographically has natural resources that are very vast and pleasant. Various tourist destinations adorn many, ranging from natural, historical/religious, and culinary tourism. Likewise, local regulations are also included. However, the thematic tourism model is still not implemented in Sumenep Regency, so seeing the potential and variety of tourist destinations in Sumenep Regency, there is a need to form a thematic tourism model along with regulations. Local regulations are used to answer the question of the development of current life and help the community's economy to be more delivered.